Prozessakten, Parteien, Partikularinteressen Höchstgerichtsbarkeit in der Mitte Europas vom 15. bis 19. Jahrhundert - Denzler, Alexander 1979- (bibliothek altes Reich, 2015)
The essays in the volume give an overview of current legal historical research on supreme jurisdiction in the Holy Roman Empire from the 15thto the 19thcenturies. For the first time, they provide a comparative presentation and analysis of the Imperial Chamber Court (Reichskammergericht), the Aulic Council (Reichshofrat), along with other supreme courts and numerous appellate courts. Alexander Denzler, Universität Eichstätt-Ingolstadt; Ellen Franke, Universität Wien; Britta Schneider, Universität Würzburg.